The Formulation of a Dynamic Portfolio between Gold and Stocks on the Indonesia Stock Exchange during the COVID-19 Pandemic - Suryani, Cyndi; Robiyanto, Robiyanto (LPPM Universitas Terbuka, 2021)
COVID-19 pandemic made investor to be careful to choose the portfolio instrument. A portfolio that is formed by the right instrument certainly can minimize risks and maximize the return. This research analyzes the dynamic portfolio formed by gold and leading stocks in COVID-19 period, which is better than the the portfolio formed by stocks alone. The data used is secondary data, which is the LQ-45 index daily closing price data and world gold prices. This research also uses risk free rate data taken from bi.go.id. The analysis technique in this research is DCC-GARCH. Findings. This research concludes that stock portfolios with gold showing a good performance result with variability-based measurement.